PENGEMBANGAN SOAL BERSTRUKTUR INVESTIGASI MATEMATIKA DALAM MENYELESAIKAN MASALAH POLA BILANGAN - Cendra Kasih, Dayang Juniarti Permatasari; Sugiatno, Sugiatno; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of  this research is to develop mathematical investigation structure problem in solve the problems of pattern number. The methode that use is the research and development. The first phase in this research is self-evaluation, in the next phase is one-to-one pilot which run in parallel with experts review. Then pilot field in the small group phase. Qualitative data analisys is used in the beginning phase one-to-one and experts review, while quantitave data analisys is used in the pilot field small group. The result of this research is a mathematical investigation structure problem that is reasonable to use based on the  expert review result  and according to the mathematical investigation indicators that have been determined. While the quality of the mathematical investigation structure problem has a good quality .Keywords: Research and Development,  Problem, Mathematical Investigation, Pattern Number